BOOK REVIEWS (Journal of Finance, 1971)
Book reviewed in this article: Public Investment, The Rate of Return, and Optimal Fiscal Policy . By Kenneth J. Arrow and Mordecai Kurz. Making Monetary and Fiscal Policy . By G. L. Bach. Monetary Theory: Selected Readings . By R. W. Clower. An Essay on The Theory of Economic Prediction . By Lawrence R. Klein. Varieties of Monetary Experience . David Meiselman Inflation: The Problems it Creates and the Policies it Requires . By Arthur M. Okun, Henry H. Fowler, and Milton Gilbert. Growth Theory: An Exposition . By R. M. Solow. Liberalized Depreciation and Cost of Capital . By Eugene F. Brigham and James L. Pappas. Speculation, Hedging and Commodity Price Forecasts . By Walter C. Labys and C.W.J. Granger. Capital Budgeting: A Quantitative Evaluation of Investment Alternatives . By Robert V. Oakford. The Theory of Corporate Finance . By R. C. Stapleton. The Theory of Corporate Finance . By R. C. Stapleton. Investment Analysis ad Portfolio Management: Readings from British Publications . Edited by Basil Taylor. Economics of Financial Institutions and Markets . By Paul F. Smith. The Euro‐Dollar Market . By E. Wayne Clendenning. Stand‐by Arrangements . By Joseph Gold. The Economics of International Adjustment . Edited by Randall Hinshaw. The Responsiveness of Demand Policies to Balance of Payments: Postwar Patterns . By Michael Michaely. Foreign Investment in the Petroleum and Mineral Industries . By Raymond F. Mikesell and others. The Assessment of Land Value . Edited by Daniel M. Holland. The Analysis of Public Output , Julius Margolis Federal Tax Policy , Revised edition. By Joseph A. Pechman.